Stock market participation, inequality, and monetary policy - Davide Melcangi; Vincent Sterk (Federal Reserve Bank of New York, 2020)
What role does stock investment play in the transmission of monetary policy to the real economy? We study this question using a New Keynesian model with heterogeneous households. Following a monetary tightening, stock market participants rebalance their investments away from stocks, in line with empirical evidence on mutual fund flows. This response depresses aggregate investment and hence aggregate output and income, which feeds back into an even larger decline in stock investment. The strength of this channel is, however, highly sensitive to household heterogeneity. Therefore, we design the model to account endogenously for the observed population share of stockholders, their income characteristics, and their saving behavior. We find that, quantitatively, the stock investment channel of monetary policy dominates the consumption channels often emphasized in the literature, and also that it has become more powerful since the 1980s, as stock market participation increased.
Keywords: E21; E30; E50; E58; 330; monetary policy; stock investment; heterogeneity